Pengaruh Aplikasi Youtube Terhadap Kemampuan Komunikasi Anak Di PAUD Al-Ikhlas Desa Aektinga Kecamatan Sosa - Ikhlima Julia Ningsih; Mira Yanti Lubis; Silfa Hafizah Pulungan (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
The aim of this research is to determine: (1) The communication abilities of early childhood in PAUD Al-Ikhlas, Aektinga Village, Sosa District before being given media in the form of the YouTube application, (2) The communication abilities of early childhood in PAUD Al-Ikhlas, Aektinga Village, Sosa District after given media in the form of a YouTube application. This research uses a quantitative approach with an experimental type of research. The research design used pre-experimental with a one group pretest-posttest design type. The instruments used consist of observation, documentation and tests. The data analysis technique uses descriptive statistics and carries out prerequisite tests, namely the normality test and homogeneity test. Test the hypothesis using the "t" test. The population of this study were children at PAUD Al-Ikhlas, Aektinga Village, Sosa District. The results of the research show that: the communication skills of early childhood in PAUD Al-Ikhlas, Aektinga Village, Sosa District, are developing well. This can be seen from the results of observations of the development of children's communication skills during the pretest and posttest. The average observation results during the pretest were 24 and the average observation results during the posttest were 32. Based on the hypothesis test calculations carried out, Tcount = 16.11 by looking at t and the significance level α = 0.05 was obtained Ttable = 1 .98. because Tcount > Ttable then Ho: rejected, Ha: accepted so it can be concluded that there is an influence of the YouTube Application on Early Childhood Communication Ability in Al-Ikhlas PAUD Aektinga Village, Sosa District.